2012
DOI: 10.1007/s00253-011-3788-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a library of fungal β-glucosidases in Saccharomyces cerevisiae for the development of a biomass fermenting strain

Abstract: Converting cellulosic biomass to ethanol involves the enzymatic hydrolysis of cellulose and the fermentation of the resulting glucose. The yeast Saccharomyces cerevisiae is naturally ethanologenic, but lacks the enzymes necessary to degrade cellulose to glucose. Towards the goal of engineering S. cerevisiae for hydrolysis of and ethanol production from cellulose, 35 fungal β-glucosidases (BGL) from the BGL1 and BGL5 families were screened for their ability to be functionally expressed and displayed on the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Using this system, several proteins, including xylose isomerase (Ota et al, 2013), laccase (Nakanishi et al, 2012), and expansin-like protein , have been displayed on the yeast cell surface. Although numerous technologies for surface display systems have been reported of late (Fushimi et al, 2013;Qiu et al, 2014;Wilde et al, 2012;Yi et al, 2013;Zhang et al, 2013), the development of a wider variety of display systems would broaden the potential applications of surface engineered microorganisms toward industrial applications.…”
Section: Discussionmentioning
confidence: 98%
“…Using this system, several proteins, including xylose isomerase (Ota et al, 2013), laccase (Nakanishi et al, 2012), and expansin-like protein , have been displayed on the yeast cell surface. Although numerous technologies for surface display systems have been reported of late (Fushimi et al, 2013;Qiu et al, 2014;Wilde et al, 2012;Yi et al, 2013;Zhang et al, 2013), the development of a wider variety of display systems would broaden the potential applications of surface engineered microorganisms toward industrial applications.…”
Section: Discussionmentioning
confidence: 98%
“…The resistance to Cd 2+ by displayed SMT yeast results from the enhanced adsorption of toxic heavy metal ions on their surface (Fig. 2), which is similar to the resistance to Cd 2+ by YMT and hexa-His-displaying yeast cells [17,18] Binding heavy metal ions at the cell surface is probably a mechanism of resistance like intracellular sequestration and efflux pumping [9,24,28]. The cell division of nonengineered yeasts was inhibited by 80 µM Cd 2+ [16] whereas the engineered ones lived in the 0.5 mM Cd 2+ -containing medium (Fig.…”
Section: Strainsmentioning
confidence: 93%
“…Other studies have also shown that the expression of β-glucosidase genes with signal sequence in S. cerevisiae can also confer the recombinant strain to secrete β-glucosidase and utilize cellobiose [13,27]. Wilde et al compared the activity of 35 β-glucosidases from 12 filamentous fungi such as Aspergillus niger, and Aspergillus oryzae expressed in S. cerevisiae, and found the β-glucosidase from A. niger had the highest cellobiase activity [34]. The BGL1 gene from S. fibuligera is also frequently expressed in S. cerevisiae owing to its high activity [4,11,28,36].…”
Section: Introductionmentioning
confidence: 99%